2003
DOI: 10.1046/j.1523-1739.2003.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Effects of Clearcutting and Alternative Silvicultural Practices on Terrestrial Salamander Abundance

Abstract: Several studies have demonstrated the negative effects of clearcutting on terrestrial plethodontid salamander populations. However, none has experimentally compared clearcutting with multiple alternative timber-harvest methods. Using a randomized, replicated design, we compared the short-term effects (1-4 years after harvest) of clearcutting to effects of leavetree, group selection, and two shelterwood cuts on terrestrial salamanders in the southern Appalachian Mountains of Virginia and West Virginia (U.S.A.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 37 publications
5
66
1
1
Order By: Relevance
“…There are fewer studies of the potential mechanisms that give rise to these changes, and several non-competing mechanisms may explain reductions in post-harvesting amphibian abundance and diversity, such as emigration from cleared forests, loss of breeding wetlands and failed recruitment, behavioral changes, or demographic changes. Whereas Knapp et al (2003) found no significant effects of harvesting on the demography of terrestrial plethodontid salamanders, Homyack and Haas (2009) found that juveniles were more abundant in unharvested treatments. The results of Homyack and Haas (2009) suggest that lower adult survival and fecundity, or lower juvenile recruitment, may explain the lack of juveniles in harvested areas.…”
Section: Discussionmentioning
confidence: 88%
“…There are fewer studies of the potential mechanisms that give rise to these changes, and several non-competing mechanisms may explain reductions in post-harvesting amphibian abundance and diversity, such as emigration from cleared forests, loss of breeding wetlands and failed recruitment, behavioral changes, or demographic changes. Whereas Knapp et al (2003) found no significant effects of harvesting on the demography of terrestrial plethodontid salamanders, Homyack and Haas (2009) found that juveniles were more abundant in unharvested treatments. The results of Homyack and Haas (2009) suggest that lower adult survival and fecundity, or lower juvenile recruitment, may explain the lack of juveniles in harvested areas.…”
Section: Discussionmentioning
confidence: 88%
“…Most studies that examine the effects of clear-cuts on amphibians document higher abundance on control forest plots than on harvest plots, a trend that holds true for riparian forests [98,120]. deMaynadier and Hunter [118] found more than a threefold difference in amphibian abundance between control sites and clear-cuts.…”
Section: Timber Harvestmentioning
confidence: 99%
“…Perkins and Hunter [125] conjecture that partial harvest is an effective way to maintain salamander communities along headwater streams, and Patrick et al [126] found that spotted salamanders and eastern red-backed salamanders prefer uncut and partial-cut habitat, as well as retained CWD. Knapp et al [120] believe that concentrating high-intensity timber harvesting (e.g., clearcuts) in areas only a few hectares in size would minimize declines in plethodontid abundance due to timber harvest. Crawford and Semlitsch [111] suggested uneven-aged timber harvest to protect stream amphibians.…”
Section: Timber Harvestmentioning
confidence: 99%
“…Petranka et al 1993Petranka et al , 1994Pough et al 1987), and retention of full canopy cover may positively affect salamanders (Harpole and Hass 1999, Homyack and Hass 2009, Knapp et al 2003. Little or no change in salamander abundance occurred after burns (Floyd 2003, Ford et al 1999, Knapp et al 2003).…”
Section: Gulf Coastal Plainmentioning
confidence: 99%
“…Petranka et al 1993Petranka et al , 1994Pough et al 1987), and retention of full canopy cover may positively affect salamanders (Harpole and Hass 1999, Homyack and Hass 2009, Knapp et al 2003. Little or no change in salamander abundance occurred after burns (Floyd 2003, Ford et al 1999, Knapp et al 2003). A single burn increased abundance of reptiles and had no effect on numbers of amphibians in the short term (Ford et al 1999, Greenberg and Burning in many southeastern forests increased light penetration to the forest fl oor and stimulated herbaceous cover (Conner et al 2002, Wilson et al 1995, Wood et al 2004.…”
Section: Gulf Coastal Plainmentioning
confidence: 99%